2009
DOI: 10.1039/b911606k
|View full text |Cite
|
Sign up to set email alerts
|

pH-dependent assembly of 0D to 3D Keggin-based coordination polymers: Structures and catalytic properties

Abstract: Four Keggin-based coordination polymers, namely, {[Cu2(4,4'-bpy)(4,4'-Hbpy)4(H2O)4](SiW12O40)2(H2O)4}n (1), {[Cu2(4,4'-bpy)(4,4'-Hbpy)6(SiW12O40)3](4,4'-Hbpy)2(H2O)7}n (2), {[Cu2(mu2-H2O)2(4,4'-bpy)3(SiW12O40)](H2O)6}n (3) and {[Cu2(mu2-OH)(4,4'-bpy)3(SiW12O40)(H2O)] [Cu2(mu2-O)(4,4'-bpy)4(H2O)2]0.5 x (H2O)3}n (4) (4,4'-bpy = 4,4'-bipyridine) were prepared through the hydrothermal reaction of silicotungstic acid, copper(II) nitrate and 4,4'-bipyridine under different pH conditions. Coordination polymers 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(27 citation statements)
references
References 48 publications
0
26
0
1
Order By: Relevance
“…Long et al reported the synthesis of four organic–inorganic hybrid POM compounds, {[Cu 2 (4,4'-bpy)(4,4'-Hbpy) 4 (H 2 O) 4 ](SiW 12 O 40 ) 2 (H 2 O) 4 } n ( 1 ), {[Cu 2 (4,4'-bpy)(4,4'-Hbpy) 6 (SiW 12 O 40 ) 3 ](4,4'-Hbpy) 2 (H 2 O) 7 } n ( 2 ), {[Cu 2 (μ 2 -H 2 O) 2 (4,4'-bpy) 3 (SiW 12 O 40 )](H 2 O) 6 } n ( 3 ), {[Cu 2 (μ 2 -OH)(4,4'-bpy) 3 (SiW 12 O 40 )(H 2 O)][Cu 2 (μ 2 -O)(4,4'-bpy) 4 (H 2 O) 2 ] 0.5 (H 2 O) 3 } n ( 4 ), by reaction of Keggin-type [SiW 12 O 40 ] 4− polyoxoanion, Cu ion, and 4,4'-bpy under hydrothermal conditions [44]. The Cu ions and 4,4'-bpy molecules are connected to form four different types of dinuclear copper coordination cations under different pH conditions.…”
Section: Oxidation Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Long et al reported the synthesis of four organic–inorganic hybrid POM compounds, {[Cu 2 (4,4'-bpy)(4,4'-Hbpy) 4 (H 2 O) 4 ](SiW 12 O 40 ) 2 (H 2 O) 4 } n ( 1 ), {[Cu 2 (4,4'-bpy)(4,4'-Hbpy) 6 (SiW 12 O 40 ) 3 ](4,4'-Hbpy) 2 (H 2 O) 7 } n ( 2 ), {[Cu 2 (μ 2 -H 2 O) 2 (4,4'-bpy) 3 (SiW 12 O 40 )](H 2 O) 6 } n ( 3 ), {[Cu 2 (μ 2 -OH)(4,4'-bpy) 3 (SiW 12 O 40 )(H 2 O)][Cu 2 (μ 2 -O)(4,4'-bpy) 4 (H 2 O) 2 ] 0.5 (H 2 O) 3 } n ( 4 ), by reaction of Keggin-type [SiW 12 O 40 ] 4− polyoxoanion, Cu ion, and 4,4'-bpy under hydrothermal conditions [44]. The Cu ions and 4,4'-bpy molecules are connected to form four different types of dinuclear copper coordination cations under different pH conditions.…”
Section: Oxidation Catalysismentioning
confidence: 99%
“…Long et al reported the catalytic results of epoxidation of styrene over four {SiW 12 }-based compounds 1 – 4 with TBHP as oxidant. The compounds showed high catalytic activity but the main product was benzaldehyde [44]. The distribution of the products indicated that the reaction was acid sensitive.…”
Section: Oxidation Catalysismentioning
confidence: 99%
“…Their structures change from zero dimension to two dimension with chelating and bridging coordination modes. But there have been few systematic studies on the influence of the pH values of the reaction system on structures, and by tuning the pH values, the structures of the final compounds could be regulated [28][29][30][31][32][33][34][35][36]. A number of reasons that the pH values regulated the structures have reported, such as influencing the deprotonated extend of ligands [34,37], facilitating the formation of l-OH group [29], generating different conformations and coordination modes [38].…”
Section: Introductionmentioning
confidence: 97%
“…Recently, investigation on their catalytic activity has begun to attract attention. 7 The selection of organic ligand is crucial in the design and synthesis of POM-based coordination polymers. The properties of organic ligands, such as length, geometry, coordination ability and relative orientation of the donor groups play important roles in generating framework topology.…”
Section: Introductionmentioning
confidence: 99%